Revisiting ω phase embrittlement in metastable β titanium alloys: Role of elemental partitioning. (1st March 2021) - Lai, M.J.; Li, T.; Yan, F.K.; Li, J.S.; Raabe, D.
Abstract: The role of elemental partitioning between β and ω phase in embrittling an originally ductile ω-containing Ti–12Mo (wt.%) model alloy was studied using transmission electron microscopy and atom probe tomography. It is revealed that the embrittlement of this alloy already occurs after aging at 400 °C for as short as 10 min, when the size, inter-particle spacing and volume fraction of the ω particles remain almost unchanged. The origin of the aging-induced embrittlement is attributed to the significant rejection of Mo (>5 at.%) from the ω particles during aging, which leads to remarkable increase in the shear modulus (>30 GPa) of the ω particles, promoting intense plastic flow localization and facilitating crack nucleation prior to macroscopic yielding. Graphical abstract: Image, graphical abstract